Perbedaan Beban Kognitif pada Penggunaan Kata Sandi Berbasis Pola Garis dan Angka - Paulus Insap Santosa (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Most applications require users to enter a password in order to use those applications. One type of the passwords used on smartphones is based on certain line pattern. The pattern of lines that make up the password is essentially an image similar to a sequence of numbers arranged in a particular order. Just when users need to memorize a series of numbers,